2021
DOI: 10.3390/ani11092509
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Maternal Performance Traits in Commercially Farmed New Zealand Beef Cattle

Abstract: Maternal performance is a major driver of profitability in cow-calf beef cattle enterprises. The aim of this research was to evaluate the inheritance of maternal performance traits and examine the intercorrelation among reproduction, live weight, hip height, body condition and maternal contribution to calf weaning weight in 15-month-old heifers, 2-year-old cows and mature cows in New Zealand beef herds. Data were collected on a total of 14,241 cows and their progeny on five commercial New Zealand hill country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Maternal traits were a subset of those previously described by Weik et al [ 18 ], chosen based on their relevance for the New Zealand beef sector. Rebreeding performance (RB) was defined as pregnancy outcome for 2-year-old cows present at pregnancy diagnosis and was coded as a binary trait (0 = not pregnant, 1 = pregnant).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal traits were a subset of those previously described by Weik et al [ 18 ], chosen based on their relevance for the New Zealand beef sector. Rebreeding performance (RB) was defined as pregnancy outcome for 2-year-old cows present at pregnancy diagnosis and was coded as a binary trait (0 = not pregnant, 1 = pregnant).…”
Section: Methodsmentioning
confidence: 99%
“…Weik et al [ 18 ] reported genetic parameters of maternal performance including reproduction, live weight, hip height, body condition score and maternal weaning weight traits for the maternal cohort of animals as part of a large-scale nationwide progeny test. The current study builds on that research, further exploring a subset of the maternal traits for the purpose of correlation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some other environmental factors which affect growth traits in sheep include season of birth (SOB), type of birth (TOB), year of birth (YOB), age of dam (AOD) and sex of animals [ 8 , 9 ]. It is well documented that the maternal effect is crucial in estimating the direct heritability of growth and reproductive performance traits [ 10 , 11 , 12 , 13 ]. The animal models which do not account for maternal effects may overestimate direct heritability, leading to the biased prediction of response to selection [ 6 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [ 45 ] found that among similarly managed heifers, heavier animals at first calving produced slightly more milk in the first lactation than lighter ones, and more milk results in higher body weight gains of the calves. Hip height (HH) may be correlated with reproductive traits and body weight [ 46 ], which in turn may affect milk yield and calf body weight gains. The influence of calving season on body weight gains may also be observed.…”
Section: Discussionmentioning
confidence: 99%